Developmental changes of sleep spindles and their impact on sleep‐dependent memory consolidation and general cognitive abilities: A longitudinal approach. Issue 1 (5th September 2018) - Hahn, Michael; Joechner, Ann‐Kathrin; Roell, Judith; Schabus, Manuel; Heib, Dominik PJ; Gruber, Georg; Peigneux, Philippe; Hoedlmoser, Kerstin
Abstract: Sleep spindles are related to sleep‐dependent memory consolidation and general cognitive abilities. However, they undergo drastic maturational changes during adolescence. Here we used a longitudinal approach (across 7 years) to explore whether developmental changes in sleep spindle density can explain individual differences in sleep‐dependent memory consolidation and general cognitive abilities. Ambulatory polysomnography was recorded during four nights in 34 healthy subjects (24 female) with two nights (baseline and experimental) at initial recording (age range 8–11 years) and two nights at follow‐up recording (age range 14–18 years). For declarative learning, participants encoded word pairs with a subsequent recall before and after sleep. General cognitive abilities were measured by the Wechsler Intelligence Scale. Higher slow (11–13 Hz) than fast (13–15 Hz) spindle density at frontal, central, and parietal sites during initial recordings, followed by a shift to higher fast than slow spindle density at central and parietal sites during follow‐up recordings, suggest that mature spindle topography develops throughout adolescence. Fast spindle density increases from baseline to experimental night were positively related to sleep‐dependent memory consolidation. In addition, we found that the development of fast spindles predicted the improvement in memory consolidation across the two longitudinal measurements, a finding that underlines a crucial role for mature fast spindles for sleep‐dependent memory consolidation. Furthermore, slow spindle changes across adolescence were related to general cognitive abilities, a relationship that could indicate the maturation of frontal networks relevant for efficient cognitive processing. A video abstract of this article can be viewed at:https://www.youtube.com/watch?v=7NXJzm8HbIw andhttps://www.youtube.com/watch?v=iuMQY1OIJ0s Abstract : Our results demonstrate that the typical mature spindle topography with slow spindles dominating frontal areas and fast spindles centro‐parietal areas develops throughout adolescence (a). Slow spindle development appears to contribute to the generation of frontal brain networks relevant for efficient cognitive processing (b), whereas fast spindles seem to be crucial for sleep‐dependent memory consolidation as their maturation is related to more efficient sleep‐dependent memory consolidation (c).